Deep hydration of an Li7–3xLa3Zr2MIIIxO12 solid‐state electrolyte material: a case study on Al‐ and Ga‐stabilized LLZO. Issue 1 (7th December 2021) - Redhammer, Günther J.; Tippelt, Gerold; Rettenwander, Daniel
Abstract : Hydrothermally treated Al‐ and Ga‐stabilized stuffed Li garnets, nominally Li7 La3 Zr2 O12, have been investigated by single‐crystal X‐ray diffraction to determine structural and site‐occupation alterations due to Li I /H I exchange. Abstract : Single crystals of an Li‐stuffed, Al‐ and Ga‐stabilized garnet‐type solid‐state electrolyte material, Li7 La3 Zr2 O12 (LLZO), have been analysed using single‐crystal X‐ray diffraction to determine the pristine structural state immediately after synthesis via ceramic sintering techniques. Hydrothermal treatment at 150 °C for 28 d induces a phase transition in the Al‐stabilized compound from the commonly observed cubic Ia d structure to the acentric I 3 d subtype. Li I ions at the interstitial octahedrally (4 + 2‐fold) coordinated 48 e site are most easily extracted and Al III ions order onto the tetrahedral 12 a site. Deep hydration induces a distinct depletion of Li I at this site, while the second tetrahedral site, 12 b, suffers only minor Li I loss. Charge balance is maintained by the incorporation of H I, which is bonded to an O atom. Hydration of Ga‐stabilized LLZO induces similar effects, with complete depletion of Li I at the 48 e site. The Li I /H I exchange not only leads to a distinct increase in the unit‐cell size, but also alters some bonding topology, which is discussed here.